DINAMIKA CITY BRANDING KOTA SURAKARTA DALAM MENARIK MINAT BERKUNJUNG WISATAWAN - Dyah Ayu Pandansari; Eko Priyo Purnomo; Aulia Nur Kasiwi (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This study aims to identify the role of city branding in increasing the number of tourist visits in the city of Surakarta. The research method used is library research method. Data collection method used is the documentation method. The data analysis technique used is content analysis. The results of this study are city branding is an effort of a city to maintain the existence of the excellence of its region in global competition through logos, taglines, symbols, and slogans. This is an important element in the development of aspects of life in the City, as well as Surakarta, which feels that in an effort to improve the quality of the city, it is necessary to carry out branding to the international world. Thus, city branding in the city of Surakarta uses the tagline